SERVICE QUALITY THAT AFFECT SATISFACTION OF TOURIST VISITING SAFARI WORLD ZOO - Atjanathon, Denchoke; Phongpaew, Aniruth; Srisatanon, Pornpana (Journal of MCU Phetchaburi Review, 2023)
This study aims to: 1) study personal factors affecting the satisfaction of tourists visiting Safari World Zoo 2) compare the level of satisfaction of tourists classified by personal factors. 3) study the factors of service quality that affect the satisfaction of tourists. A sample was taken from 385 tourists who visited the Safari World Zoo. The data collection tool was a questionnaire. Statistics used in data analysis were mean, standard deviation, t-test, one-way ANOVA, and multiple regression analysis.The results showed that Overall, service quality has average opinions at the highest level. satisfaction of tourists visiting Safari World. Overall, it was at a high level. For tourists with different genders, ages, marital statuses, occupations, and average monthly incomes, there is no statistically significant difference in satisfaction among tourists who visit Safari World. Factors influencing in descending order were as follows: response to tourists, Understanding of customers, credibility , confidence towards service users, and concreteness